2017
DOI: 10.1186/s12917-017-1290-2
|View full text |Cite
|
Sign up to set email alerts
|

Workload of horses on a water treadmill: effect of speed and water height on oxygen consumption and cardiorespiratory parameters

Abstract: BackgroundDespite the use of water treadmills (WT) in conditioning horses, the intensity of WT exercise has not been well documented. The workload on a WT is a function of water height and treadmill speed. Therefore, the purpose of this study was to determine the effects of these factors on workload during WT exercise.Fifteen client-owned Quarter Horses were used in a randomized, controlled study. Three belt speeds and three water heights (mid cannon, carpus and stifle), along with the control condition (dry t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 29 publications
0
27
0
1
Order By: Relevance
“…If faster speeds are selected, water depth should be decreased and the gait quality and posture of the horse re-assessed as water depth is incrementally increased. It has previously been shown that increasing water depth has a greater impact on the workload of water treadmill exercise than increasing walking speed [ 19 ]. The greatest workload (as measured by oxygen consumption and heart rate) was found to occur at 1.39 m/s in water at the depth of the stifle.…”
Section: Factors Influencing Selection Of Speed Water Depth and Dmentioning
confidence: 99%
“…If faster speeds are selected, water depth should be decreased and the gait quality and posture of the horse re-assessed as water depth is incrementally increased. It has previously been shown that increasing water depth has a greater impact on the workload of water treadmill exercise than increasing walking speed [ 19 ]. The greatest workload (as measured by oxygen consumption and heart rate) was found to occur at 1.39 m/s in water at the depth of the stifle.…”
Section: Factors Influencing Selection Of Speed Water Depth and Dmentioning
confidence: 99%
“…However, the specific effects of different water-based exercise on SDFT stresses and strains are yet to be determined. Previous studies suggest that water treadmills and water walkers are classed as low-intensity exercise, 127,130 while swimming and ridden 'surge' training may be a form of relatively high-intensity exercise. 126,131 Therefore, water treadmills and water walkers may be suitable at an earlier stage of the fittening programme before ridden work commences.…”
Section: Early Intervention Strategies: Reducing Biomechanical Strementioning
confidence: 99%
“…Greco-Otto et al . (10) documented that horses exercised on a WT at different depths work at exercise intensities of 27.7–32.7% of their maximal HR, reflecting its aerobic nature.…”
Section: Types Of Horse Exercise In Watermentioning
confidence: 99%